Porcn is essential for growth and invagination of the mammalian optic cup - Fuhrmann, Sabine; Ramirez, Sara; Mina Abouda, Mirna; Campbell, Clorissa D. (Frontiers in Cell and Developmental Biology, 2022)
Microphthalmia, anophthalmia, and coloboma (MAC) are congenital ocular malformations causing 25% of childhood blindness. The X-linked disorder Focal Dermal Hypoplasia is frequently associated with MAC and results from mutations in Porcn, a membrane bound O-acyl transferase required for palmitoylation of Wnts to activate multiple Wnt-dependent pathways. Wnt/-catenin signaling is suppressed in the anterior neural plate for initiation of eye formation and is subsequently required during differentiation of the retinal pigment epithelium (RPE). Non-canonical Wnts are critical for early eye formation in frog and zebrafish, however, it is unclear whether this also applies to mammals. We performed ubiquitous conditional inactivation of Porcn in mouse around the eye field stage. In PorcnCKO, optic vesicles (OV) arrest in growth and fail to form an optic cup. Ventral proliferation is significantly decreased in the mutant OV, with a concomitant increase in apoptotic cell death. While pan-ocular transcription factors such as PAX6, SIX3, LHX2, PAX2 are present, indicative of maintenance of OV identity, regional expression of VSX2, MITF, OTX2 and NR2F2 is downregulated. Failure of RPE differentiation in PorcnCKO is consistent with downregulation of the Wnt/-catenin effector LEF1, starting around 2.5 days after inactivation. This suggests that Porcn inactivation affects signaling later than a potential requirement for Wnts to promote eye field formation. Altogether, our data shows a novel requirement for Porcn in regulating growth and morphogenesis of the OV, likely by controlling proliferation and survival. In FDH patients with ocular manifestations, growth deficiency during early ocular morphogenesis may be the underlying cause for microphthalmia.